Circulatory support using the impella device in fontan patients with systemic ventricular dysfunction: A multicenter experience. Issue 1 (23rd January 2017) - Morray, Brian H.; Dimas, Vivian V.; Lim, Scott; Balzer, David T.; Parekh, Dhaval R.; Van Mieghem, Nicolas M.; Ewert, Peter; Kim, Dennis W.; Justino, Henri; McElhinney, Doff B.; Jones, Thomas K.
Abstract : Background: There are limited mechanical circulatory support options for patients with single ventricle (SV) anatomy. This is a multicenter, retrospective study of the Impella pump to support the systemic ventricle in a cohort of SV patients with Fontan circulation. Methods: Patients with SV anatomy supported with an Impella device from 2012 to 2015 were included. Demographic information, indication for support, adverse events and short‐term outcome data were collected. Results: Ten patients were included. The median age and weight at implant was 26 years (4‐38 years) and 64 kg (15–102 kg). Indications for support were systemic ventricular failure with cardiogenic shock ( n = 8) or high‐risk electrophysiology (EP) procedures ( n = 2). The median duration of support was 49 hr (2.7–264 hr). Support was discontinued for ventricular recovery in five patients, transition to another device in two patients, completion of EP procedure in two patients and death in one patient. Survival to hospital discharge was 80%. Adverse events occurred in 4 patients. There were two cases of hemolysis, one case of increasing aortic valve insufficiency with implant and one asymptomatic access site thrombus. There were no bleeding or thromboembolic events. Conclusions: Impella devices can provide temporary support for the systemic ventricle in SV patients as a bridge to recovery or additional device. Procedural survival and adverse event profiles are favorable. © 2017 Wiley Periodicals, Inc.